An Examination of Per Capita Income Convergence in Emerging Market Economies. (September 2022) - Sharma, Prakarti; Sharma, Nidhi
The study intends to examine the convergence of per capita income in emerging market economies (EMEs) toward a steady state for the post reform period (1999–2019). Cross-sectional regression analysis has been performed for unconditional convergence and a panel data regression to find the conditional convergence in EMEs. Sigma convergence has been applied to find the dispersion of income level in EMEs. In addition, to find the impact of global financial crisis on the convergence process of EMEs, unit root test with one structural break has been applied. The findings indicate that there exists unconditional convergence among EMEs toward a common steady state. Further, the results show a significant role of all control variables except education in the growth process but prove the absence of conditional convergence in selected EMEs. The results of sigma convergence find that the dispersion of per capita income is declining in EMEs, showing the sign of sigma convergence in EMEs. However, this study provides further scope to examine per capita income convergence among EMEs by including other variables and their effect on the convergence process of EMEs.